2012
DOI: 10.1155/2012/568106
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Side Effects of Chinese Herbal Medicine for Menopausal Symptoms: A Critical Review

Abstract: This study evaluates 23 (9 Chinese and 14 non-Chinese) randomized controlled trials for efficacy and side effects of Chinese herbal medicine on menopausal symptoms. Menopause was diagnosed according to western medicine criteria in all studies while seven Chinese studies and one non-Chinese study further stratified the participants using traditional Chinese medical diagnosis “Zheng differentiation.” Efficacy was reported by all 9 Chinese and 9/14 non-Chinese papers. Side effects and adverse events were generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 57 publications
0
11
1
1
Order By: Relevance
“…The main findings of this review do not completely echo the results from previous reviews (Peng 2014; Taylor-Swanson 2014; Xie 2005; Xu 2012). Whilst this review is likely the most comprehensive systematic review with meta-analysis, it found little evidence that CHM was any more or less efficacious for the management of menopausal symptoms compared to placebo or HT.…”
Section: Discussioncontrasting
confidence: 98%
“…The main findings of this review do not completely echo the results from previous reviews (Peng 2014; Taylor-Swanson 2014; Xie 2005; Xu 2012). Whilst this review is likely the most comprehensive systematic review with meta-analysis, it found little evidence that CHM was any more or less efficacious for the management of menopausal symptoms compared to placebo or HT.…”
Section: Discussioncontrasting
confidence: 98%
“…However, there remain doubts about the effi cacy of TCM in managing menopausal symptoms, although promising results in clinical practice have emerged 15 . Randomized, clinical trials (RCTs) have found positive fi ndings concerning the effectiveness of CHM for symptomatic menopausal women with mild side-effects 16 -18 , but these studies appear methodologically weak 19 and the urgent necessity to conduct more large-sampled RCTs in this area has been identifi ed 20,21 . Research has revealed both positive and negative fi ndings with regard to the effi cacy of acupuncture for hot fl ushes (an area attracting the most attention amongst the majority of clinical studies on acupuncture for symptomatic menopausal women) 22 -25 .…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, however, kansui affected cardiac and hepatic function and it affected the histomorphology of the heart, liver, and kidneys in rats (68). The authors of a review concluded that the major adverse reactions to TCMs were gastrointestinal symptoms including abdominal bloating or pain, epigastric discomfort, and stomach disorder, followed by diarrhea, headaches, nausea, breast distension or pain, abnormal vaginal bleeding, and dizziness (69). In a randomized controlled trial, Li et al reported that Tongxinluo Capsules, a TCM used to treat coronary disease and angina pectoris, caused an adverse reaction in the form of stomachaches in the treatment group (70).…”
Section: Adverse Reactionsmentioning
confidence: 99%